Implementation of a Service-Oriented Architecture for Applications in Physical Rehabilitation (2017)
Currently, the interest in service-oriented architectures (SOA) has risen due to their structural flexibility, which allows to obtain features such as scalability, fault tolerance, low coupling, and easy integration, among others. In this context, this article presents the implementation of a SOA for tele-operated physical rehabilitation applications; this SOA ensures an effective orchestration of services, adding special functions, such as synchronous tele-operation of machines for physical rehabilitation, in such a way that it can be adapted and implemented by using information and communication technologies (ICT). The implementation of the architecture was validated by means of a test that allowed to analyze the behavior of the web services defined for the application.